Projected sensitivity of the LUX-ZEPLIN experiment to the 0νββ decay of 136Xe - Akerib,DS; Akerlof,CW; Alqahtani,A; Alsum,SK; Anderson,TJ; Angelides,N; Araújo,HM; Armstrong,JE; Arthurs,M; Bai,X; Balajthy,J; Balashov,S; et al. (Physical Review C, 2020)
The LUX-ZEPLIN (LZ) experiment will enable a neutrinoless double β decay search in parallel to the main science goal of discovering dark matter particle interactions. We report the expected LZ sensitivity to 136Xe neutrinoless double β decay, taking advantage of the significant (>600 kg) 136Xe mass contained within the active volume of LZ without isotopic enrichment. After 1000 live-days, the median exclusion sensitivity to the half-life of 136Xe is projected to be 1.06×1026 years (90% confidence level), similar to existing constraints. We also report the expected sensitivity of a possible subsequent dedicated exposure using 90% enrichment with 136Xe at 1.06×1027 years.